COMPARISON OF ANDROGEN AND ESTROGEN RECEPTORS’ EXPRESSION IN DARTOS TISSUE OF BOYS WITH AND WITHOUT HYPOSPADIAS - Danurdoro, Aria; Ghinorawa, Tanaya; Yuri, Prahara; Setyo Hariyanto, Didik; Rodjani, Arry; Wahyudi, Irfan; Immanuel Hutasoit, Yonas; Yudha Alfanius Hutahaean, Andre (Indonesian Journal of Urology, 2023)
Objective: This study aims to investigate the characteristics of androgen receptors (AR), estrogen receptor 1 (ER1) and estrogen receptor 2 (ER2) expression in dartos tissue of patients with congenital hypospadias, compared to normal penis. Material & Methods: We harvested 63 dartos tissue consisting of 53 congenital hypospadias that underwent urethroplasty (20 distal and 33 proximal) and 10 normal penis that underwent circumcision as controls from September 2017 to September 2018. The expressions of AR, ER1, and ER2 were measured using Quantitative Real-Time PCR (qPCR). All data were analyzed by Prism 7, and one-way ANOVA tests were used to compare gene expressions between the groups. Results: The mean age was 68.99 (± 45.5) and 65.6 (± 25.8) months in boys with and without hypospadias, respectively. The expression of mRNA AR was decreased in proximal (6.26 ± 2.30) and distal hypospadias (6.43 ± 2.22) compared to controls (9.69 ± 1.10), which were statistically significant (p=0.0001 and p<0.0001, respectively). We found a statistically significant difference of ER1 expression compared to controls (p=0.0064). The expression of ER2 was significantly increased in distal (21.03 ± 5.00) and proximal hypospadias (25.21 ± 8.06) groups compared to controls (11.80 ± 2.49) (p<0.0001). There was no statistically significant mean difference in mRNA ER1 expression (p=0.65). Conclusion: The repressed AR and elevated ER mRNA as shown in our study may suggest that defects in those receptors’ interaction and/or balance may contribute to hypospadias and penile curvature condition. Further studies are needed to evaluate any gene-related problems in hypospadias. Keywords: Hypospadias, androgen receptor, estrogen receptor, dartos tissue.